2012
DOI: 10.2174/1874364101206010054
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Bevacizumab Through Nanospheres for Extended Treatment of Age-Related Macular Degeneration

Abstract: Bevacizumab (Avastin®) has been used by ophthalmologists in many countries as an off-label drug for the treatment of wet age-related macular degeneration (AMD). Due to its short half-life necessitating frequent intravitreal injection, a method for sustained delivery is in need. We demonstrated that bevacizumab could be released in a sustained fashion over 90 days from nano- and microspheres fabricated from poly(DL-lactide-co-glycolide) and poly(ethylene glycol)-b-poly(D,L-lactic acid), respectively. The drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 29 publications
7
64
0
1
Order By: Relevance
“…One possible strategy to overcome these problems resides in the antibody encapsulation into biodegradable and biocompatible polymers creating a tailorable nanosystem. [15][16][17] In this way, the loaded antibody is protected from degradation and from interaction with the immune system and can be released in a controlled manner. Poly(lactic-co-glycolic) acid (PLGA) is an excellent candidate, as it has been approved by FDA for human use because of its biodegradability and low systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…One possible strategy to overcome these problems resides in the antibody encapsulation into biodegradable and biocompatible polymers creating a tailorable nanosystem. [15][16][17] In this way, the loaded antibody is protected from degradation and from interaction with the immune system and can be released in a controlled manner. Poly(lactic-co-glycolic) acid (PLGA) is an excellent candidate, as it has been approved by FDA for human use because of its biodegradability and low systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier degradation rate on the one side, and the bevacizumab release rate on the other side, is very important because: (i) bevacizumab presents a short halflife (Li et al, 2012), (ii) a slow degradation of a carrier assures a prolonged drug delivery, and (iii) it assure low concentrations of degradation products in patient body.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of bevacizumab-loaded PLGA nanoparticles was studied (Li et al, 2012) during a 100 days experiment. It was found that polymer carriers' degradation rate increases when the molar mass decreases (Lao et al, 2011); the carriers' size can be easily adjusted to lower values and thus can easily penetrate through cornea, but the yield of encapsulation decreases when the carriers' size decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Gefitinib has also been encapsulated in PLGA nanoparticles for the treatment of lung and skin carcinoma [90]. Bevacizumab has been encapsulated in PLGA nanoparticles, liposomes, and poly(ethylene glycol)-b-poly(D,L-lactic acid) microspheres for the treatment of age-related macular degeneration [91][92][93]. However, neither gefitinib nor bevacizumab have been encapsulated in polymeric microspheres for intracranial tumor therapy.…”
Section: Chemotherapeutic Choicementioning
confidence: 99%